NEONATAL MORTALITY: BIOLOGICAL AND CARE CHARACTERISTICS OF THE NEW-BORNS AND THEIR MOTHERS - Mayrene Dias de Sousa Moreira; Maria Aparecida Munhoz Gaíva; Rossana Marchese Bittencourt (Universidade Federal do Paraná, 2012)
A transversal-descriptive study with a quantitative approach, with the objective of analyzing the biological- and care characteristics of live new-borns who died in the post-partum period in the town of Cuiabá in the state of Mato Grosso in 2010. The data was obtained form Certificates of Live Birth, Death Certificates and hospital notes from February to April 2011, organized in Excel 2007 and submitted to analysis via descriptive statistics. There were 77 neonatal deaths, of which 72.8% took place in the first week of life. 71.5% of the babies had a birth weight of below 2,500g, and 75.3% were born at less than 38 weeks. 51.9% of the births were caesarean. The majority of the newborns received care during birth; however, most had some degree of asphyxia on being born and needed cardiopulmonary resuscitation. Knowledge of the factors related to neonatal mortality can contribute to its prevention.